تحليل الرسالة الإعلامية تأثير الفضائيات العربية على الشباب العربي - المسفر, محمد (revue mofakir; No 03 (2008): مجلـــة المفكــر, 2018)
تحليل الرسالة الإعلامية تأثير الفضائيات العربية على الشباب العربي